Bis[μ-2-(2H-benzotriazol-2-yl)-4-methylphenolato]bis[dimethylaluminium(III)] - Li, Chen-Yu (International Union of Crystallography, 2009)
The title complex, [Al(2)(CH(3))(4)(C(13)H(10)N(3)O)(2)], is dimeric, bridged through the O atoms of the phenolate anions. The asymmetric unit contains one half of the molecule and there is a crystallographic inversion centre in this molecule. Each Al atom is pentacoordinated by one N atom and two bridging O atoms of two N,O-bidentate benzotriazolylphenolate ligands and by two C atoms from two methyl groups, forming a distorted trigonal–bipyramidal environment.